Rereading Narratives of Safety and Security in Ancient Israel from a Pastoral Perspective - Rugwiji, Temba T. (Journal for Semitics, 2018)
<span style="font-family: 'Times New Roman',serif; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: EN-US; mso-bidi-font-size: 12.0pt; mso-ansi-language: EN-ZA; mso-bidi-language: HE;">The present study investigates the concept of safety and security in the Hebrew Bible in order to demonstrate that our concern for self-defence in the modern post-biblical world was also a prerogative among biblical societies. Numerous inferences to self-defence in the Hebrew Bible show that ancient Israelite societies did not take preparedness against enemy attack lightly. In this essay, lessons on safety and security drawn from ancient Israelite societies will be appropriated in the Zimbabwean context. This appropriation is necessary because safety and security was critical in ancient Israel as it is in our post-colonial Zimbabwean society. Constructive themes from the Hebrew Bible will be appropriated as lessons to be learnt from the narratives about ancient Semitic peoples who are purported to have lived in a â€œrealâ€ physical, yet historical, space. Admittedly, the biblical text depicts that bad/negative things happened in ancient Israel. However, in this study self-defence is explored in a positive light in order to sensitise modern societies to the importance of preparedness against potential aggressors. In addition, the study attempts to encourage the readership to conceptualise ideals of moral values and high ethical integrity which the biblical text seeks to promote. Having said that, some pastoral perspectives on safety and security, as well as self-defence, are also explored.